Improving English Reading Comprehension of Chinese Undergraduates through the Use of Translanguaging in English Reading Instruction - Wang, Jingxuan; Ekkayokkaya, Maneerat (An Online Journal of Education, 2025)
The objectives of this research were to: 1) investigate the effects of translanguaging in improving English reading comprehension among Chinese undergraduates, and 2) explore the opinions of Chinese undergraduates towards the use of translanguaging in English reading instruction. The participants were 42 non-English major undergraduates from a provincial university in southwest China, selected through purposive sampling, as they were all enrolled in the same College English Reading and Writing course taught by the researcher. The instruction lasted for nine weeks and was implemented within the Preview-View-Review (PVR) framework in English reading instruction. The instructional instrument included lesson plans, while the research instruments included pre- and post-tests of English reading comprehension, and semi-structured interviews. The research results indicated that 1) the students achieved substantially higher scores on the English reading comprehension test following the use of translanguaging in English reading instruction, and 2) the students had a positive attitude towards the use of translanguaging in English reading instruction, particularly in enhancing understanding and learning efficiency, reducing learning pressure, and increasing learning interest. These findings highlight the pedagogical potential of incorporating translanguaging in English reading instruction. Further research is recommended on its application in different educational contexts.